Creating common epistemic spaces through multimodal stance-taking practices - Ushchyna, Valentyna (Bloomsbury, 2024)
The chapter, written by Valentyna Ushchyna, stands out in this volume, as it deals rather with real-life online communication than with artistic discourse. The author shows the linguistic ways epistemic stancetaking becomes an integral part of the shared epistemic spaces creation, where the dynamics and ecology of meaning-making presupposes interaction and collaboration. To be more specific, the focus of this study is on the epistemic stancetaking in COVID-19 discourse. Because knowledge concerning COVID-19 is insufficient, epistemic possibilities build upon uncertainty and unpredictability. The study uses objective hermeneutic approach as the methodological framework that allows disclosing of the concealed structures of discourse and enables explanation of the complex processes of social semiosis in post-modern computerized society. Within objective hermeneutic paradigm, analysis of stancetaking presupposes taking into account personal attitudes of individual speakers (stance-takers) along with the domineering social structures framing their discursive actions and interactions.
Keywords: stance; stancetaking; epistemic stance; epistemic space; modality; evidentiality